Der Karst der humiden heissen und sommerheißen Gebiete Ostasiens - von Wissmann, Hermann (ERDKUNDE, 1954)
Karst regions of the humid tropics and summerhot perhumid subtropics mostly (not in marly limestone f. i.) show features different from karst topography in any other climate: They show a dissolution into hillocks or cones or turrets, towers and castles, which are more or less regularly arranged and often of similar or same height and even size in o n e area. This is the Kegelkarst or karst à pitons. The boundary of its occurrence in China (Taihu — south of Nanking — including Kweichow, E. Yunnan, excluding Central Yunnan) runs along the margins of the climates mentioned above, thus showing its dependence on climate, its being a feature of climatical geomorphology. Of the various formations of kegelkarst, two widely differ in appearance from one another: 1. A low karst with rounded hillocks of even height (300 ft f. i.). The hillocks are separated from each other by shallow enclosed depressions (dolines). This is the „cockpit“-karst(karst écumoire) of Jamaica, Porto- rico, Java and New Guinea. A similar karst, with conical hills (like hundreds of pegtops turned upside down), and deeper dolines between, is common in Kweichow and E. Yunnan. In the mountains of Laos and N. Vietnam, of regions of recent strong uplift, there is a wild, almost un- passable karst of peaks deeply furrowed by lapiez and of precipitous abysses. 2. A river plain, dotted with groups or swarms of limestone towers or castles (200 to 700 ft. high), isolated from each other by the plain (fig. 4, 5), to which they fall down in vertical walls. This is the tower karst, Turmkarst or karst a tourelles. Its principal domain are the basins of Kwangsi. But it also occurs in Vietnam, Siam, Tenasserim, Malaya, Central Sumatra and in Cuba. The bedding planes of the towers may vary from horizontal to vertical. The contrast of the ricefield plain and the picturesque towers has often incited Chinese painting. In the level of the plain, the towers are undermined by grottoes and horizontal caves. So the plain grows by undercutting (lateral erosions) due to dissolution of limestone. In the Bay of Halong (NE Tongking) all transitions from wild moutain-karst to tower-karst can be studied. Dolines reaching the level of active caves are enlarged into uvalas (poljes) in this level, until the walls dividing the uvalas from one another or from the marginal plain break down and vanish (fig. 2, 3). The plain is partly replaced by a very shallow sea, with flats, dry during low tide. The surf is undermining quicker than running and stag- nant water of the plains. 3. While being laterally enlarged by undercutting, the limestone plane is buried by residues and deposits. The final stage of this cycle is a buried limestone plane (Überschüttungsebene, plane de recouvement). Where the limestone surface has been excavated in the tin mines of Malaya, one sees a field of pinacles, sometimes 50 ft high, with deep pockets between. Where such a pinacle-area is exhumated by erosion, it becomes a wild area of lapiez, like the stone forest round Lunan in E. Yunnan. 4. When a limestone river-plane gets out of action, because the river has cut down into the underlying limestone, or because the flowing water sinks down into cavities, the karst towers loose their vertical walls, and their bases become surrounded by debris slopes (fig. 7).